Effect of yttrium‐90 radioembolization on outcomes in Asian patients with early to advanced stage hepatocellular carcinoma. Issue 5 (2nd August 2016) - Woo, Hyun Young; Kim, Do Young; Heo, Jeong; Kim, Chang Won; Kim, Suk; Yoon, Ki Tae; Lim, Won; Hong, Young Mi; Won, Jong Yun; Lee, Sangheun; Han, Kwang Hyub; Cho, Mong
Abstract : Aim: The aim of this study was to investigate the effect of yttrium‐90 radioembolization on the outcome of Asian patients with early to advanced stage hepatocellular carcinoma (HCC). Methods: Sixty‐two patients were screened and 50 patients (80.6%) were eligible. Response was evaluated using the Response Evaluation Criteria in Solid Tumors (RECIST), and overall survival was estimated using the Kaplan–Meier method. Results: The Barcelona Clinic Liver Cancer (BCLC) stage was A in 40% of patients, B in 24%, and C in 36%; 66% of patients had hepatitis B virus infections. According to RECIST criteria, partial responses occurred in 40% of patients, and stable disease was achieved in 46%. Tumor response was significantly associated with BCLC stage ( P = 0.003). The median overall time to progression was 5.8 months (range, 0.9–46.1 months). Follow‐up treatments after radioembolization were carried out in 31 patients due to remnant HCC ( n = 18) or HCC progression ( n = 13). The median overall survival was 40.9 months (95% confidence interval, 10.2–71.6 months). Treatment was tolerable except for one lung toxicity and two hepatic toxicities. Conclusion: Yttrium‐90 radioembolization appears to be well tolerated and effective in Asian patients with BCLC stage A–C HCC. Follow‐up treatments after radioembolization can be safely provided.